Sketches for a Portrait of Hanoi - Hữu Ngọc. (Hà Nội : Thế giới, 1998)
Myths Die Hard. Strolling in the Ancient City of the Dragon. The Rural Belt. Citadels and Palaces. The Former Quarter of Westerners. Mutations.
Keywords: Văn hoá; Hà Nội; Culture; Hanoi (Vietnam) -- Culture